Life history traits of South African Encephalartos spp. (Zamiaceae) and their implications for understanding population structure, responses to threats and effective conservation action - Konings, Kim Martina (Plant Conservation Unit (PCU), 2016)
Understanding life history traits and how they influence population-level processes under different conditions have been important areas of study in evolution and ecology. One application in ecology has been to determine whether there are general responses that apply to species with similar life history traits, which could provide a predictive understanding of species with shared traits rather than having to adopt a speciesspecific approach to management. In this study, an analysis of life history traits was applied to cycads, the oldest living seeds plants which are at risk of extinction due to vulnerability to illegal wild harvesting and habitat loss. The study focused on South African cycad species within the genus Encephalartos, as well as two species from Swaziland. The first objective was to identify groups of species with similar life histories and to assess whether these groups are aligned with phylogenetic relationships or an association with particular environments. The second objective was to determine whether species with shared suites of life history traits exhibited a similar population stage structure. Hierarchical cluster analysis and Principal Component Analysis (PCA) were used to identify groups based on key life history traits, namely, cone number and coning interval, number of seeds produced, number of stems, stem height and plant habit. Four life history groups emerged, these were: Group 1 with single-stemmed, subterranean species such as E. villosus; Group 2 generally characterised by medium-height species with many stems such as E. lehmannii; Group 3 with the tallest species which generally produce the most cones at the most frequent interval such as E. natalensis; and Group 4 with dwarf-arborescent, multi-stemmed species such as E. horridus. The groups were not found to correspond with the most recent phylogeny for Encephalartos and thus phylogenetic constraints were excluded. An analysis of environmental variables for 193 populations of species in all groups, including maximum and minimum temperatures, mean annual precipitation, moisture index, rainfall co-efficient of variation and fire return frequency, showed that the means per group were not significantly different from each other for most of the variables. However, it was evident that the variable ranges showed clear trends with biological significance. These tended towards more stable, less variable environments with more predictable rainfall for Group 1 species, and less stable, more variable environments with less predictable rainfall for species within Group 4. Groups 2 and 3 showed a large range and overlap in environmental associations with no consistent patterns. Population structure is valuable for determining whether recruitment in a population is adequate for species survival. Static life tables and Chi-Squared analyses were used to test differences in the population structure and survivorship patterns of species between and within the life history groups. If particular demographic patterns were shown to be emergent properties of certain suites of life history traits, autecological studies may be avoided for predictive-ecological conservation frameworks. The results showed that species in Group 1 had populations with a high proportion of juveniles and fewer reproductive adults, indicating high recruitment as well as high juvenile mortality. In contrast, species in Group 4 had populations with a high proportion of adults and fewer juveniles indicating low recruitment and high juvenile mortality with primary investment into adult plant persistence through vegetative suckering. Group 2 consisted mostly of rare species with very small populations and high proportions of adult plants showing evidence of episodic recruitment events. Species in Group 3 showed a similar trend towards intermittent recruitment with adult persistence, however, no explicit population structure emerged. This led to the conclusion that Groups 1 and 4 are relatively consistent and predictable, however, Groups 2 and 3 would better benefit from an autecological approach to management. This study was helpful to assemble life history data for South African Encephalartos, as well as environmental parameters for each species. Ultimately, it has shown that primary investment into seeds versus persistence, or a combination thereof, can influence population structure.